2009
DOI: 10.5424/sjar/2009072-430
|View full text |Cite
|
Sign up to set email alerts
|

Phytostabilization of cadmium contaminated soils by Lupinus uncinatus Schldl.

Abstract: Phytoremediation offers the benefits of being in situ, low cost and environmentally sustainable. Lupinus species is starting to generate interest for phytoremediation of soils showing intermediate metal pollution. The aim of this study was to explore the accumulating behavior and tolerance of Lupinus uncinatus Schldl. towards increasing Cd concentrations in soil. For this purpose the effects of different Cd treatments on plant growth, survival, metal tolerance, Cd accumulation and distribution in various plant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 17 publications
0
6
0
3
Order By: Relevance
“…Estudios realizados en especies de los géneros Lupinus, Solanum y Brassica siguieron comportamientos similares a los previamente descritos, tal fue el caso de Lupinus uncinatus, el cual cuando fue evaluado con diferentes concentraciones de cadmio aplicado al suelo, presentó inhibición del crecimiento en longitud de planta y en número de hojas; consecuentemente, el cadmio también influyó significativamente en el rendimiento de la materia seca en raíces, hojas y tallos (Ehsan et al 2009).…”
Section: Discussionunclassified
“…Estudios realizados en especies de los géneros Lupinus, Solanum y Brassica siguieron comportamientos similares a los previamente descritos, tal fue el caso de Lupinus uncinatus, el cual cuando fue evaluado con diferentes concentraciones de cadmio aplicado al suelo, presentó inhibición del crecimiento en longitud de planta y en número de hojas; consecuentemente, el cadmio también influyó significativamente en el rendimiento de la materia seca en raíces, hojas y tallos (Ehsan et al 2009).…”
Section: Discussionunclassified
“…This may suggest that the observed pattern of Cd partitioning is a plant strategy to counter toxicity as also suggested by Zornoza et al (2002). The Cd uptake in the lupin roots serves to offer the benefit of metal phytostabilization (Ehsan et al 2009). …”
Section: Zn and CD Distribution In Various Plant Partsmentioning
confidence: 95%
“…Overall, the results support the hypothesis that L. uncinatus could be used in the combined strategies to recover Zn-and Cd-contaminated soils. The use of L. uncinatus could associate the advantages of using leguminous plants and the efficiency in phytostabilization (Ehsan et al 2009) as also demonstrated for other trace elements in the case of white lupin (Vazquez et al 2006;Esteban et al 2008) and also in case of other plants such as Viguiera dentata, Parthenium bipinnatifidum, Flaveria angustifolia, F. trinervia, and Sporobolus indicus which could be used to vegetate soils with large amounts of As, Cu, Pb, and Zn (Franco-Hernández et al 2010). Its efficiency in accumulating Cd in the roots, with very low translocation rate to the shoots, could make it a good choice in phytostabilization, preventing leaking of Cd from contaminated soils.…”
Section: Zn and CD Distribution In Various Plant Partsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lupinus chamissonis enhances biodegradation of hydrocarbon‐contaminated groundwater, possibly by stimulating the hydrocarbon‐degrading microorganisms in the soil (Hoffman, 2004). Lupines such as L. uncinatus Schltdl., a species native to Mexico (Alderete‐Chavez et al, 2008) have also been studied for their potential for in situ metal phytostabilization (or immobilization), which helps prevent erosion, reduce airborne movement, and leaching of pollutants (Ehsan et al, 2009), allowing plants with lower uptake of metals to be used to prevent transfer into the environment. Lupinus albus is suitable for the initial phytoimmobilisation of heavy metals in a calcareous soil with high levels of zinc and lead (Martínez‐Alcalá et al, 2009).…”
Section: Lupines As Phytoremediation Agentsmentioning
confidence: 99%